A. \( - \frac{1}{2}\)
B. \( - \frac{1}{4}\)
C. \(\frac{4}{5}\)
D. \(\frac{1}{5}\)
B
\(\begin{array}{l}\int\limits_0^1 {\frac{{xdx}}{{{{\left( {x + 3} \right)}^2}}}} = \int\limits_0^1 {\frac{{x + 3 - 3}}{{{{\left( {x + 3} \right)}^2}}}dx} \\ = \int\limits_0^1 {\frac{{dx}}{{x + 3}}} - 3\int\limits_0^1 {\frac{{dx}}{{{{\left( {x + 3} \right)}^2}}}} \\ = \left. {\left( {\ln \left| {x + 3} \right| + \frac{3}{{x + 3}}} \right)} \right|_0^1\\ = \ln 4 + \frac{3}{4} - \ln 3 - 1\\ = - \frac{1}{4} - \ln 3 + \ln 4\end{array}\)
\( \Rightarrow a = - \frac{1}{4},\,\,b = - 1,\,\,c = 1\)
Vậy \(a + b + c = - \frac{1}{4} - 1 + 1 = - \frac{1}{4}\).
Chọn B.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247